A atualidade da indústria cultural e os limites da produção capitalista - Crioni, Renato (Universidade Federal de São Carlos, 2014)
The concept of Cultural Industry was born from the experiences of Horkheimer and Adorno during their exile in the United States, following the rise of National Socialism and the eruption of the Second World War. They verified the enhanced and expanded understanding of life's spontaneous character in the mold of modern commodity production. They attributed the concept of cultural industry: Its products, being goods themselves, also legitimate the abstract capitalist order, which its participants - social beings - experience as a determinately subjective expression. The cultural industry would be a manifestation of the very development of the productive forces which is consolidated in the Keynesian-Fordist administered society of labor and large-scale consumption, and the so-called welfare state. Thus the issue being examined in this study is presented: Half-formation (Halbbildung) and cultural industry in the (hypothetical) context of the objective limits of the capitalist mode of production. However, according to the usual interpretations, would the products of the cultural industry be a lasting solution for the bottlenecks of capital appreciation? The central hypothesis is that the "colonization" of the commodity form by virtually every human manifestation, as the concept of cultural industry seeks to comprehend, expresses the very objective limits of the capitalist mode of production, not only in our current times, but also in retrospect, at the origin of the concept formulated in the 1940s by Horkheimer and Adorno. This is, therefore, a theoretical-reflexive study on sociological issues, conducted through the analysis of economic transformations - especially in the spheres of work and free time - and how this combination determines the manner in which the cultural industry conditions half-formation, whose processes - within the scope of the microelectronics revolution and of the imagistic shock - affect our perceptual apparatus and the core of our psyche.
The current state of the cultural industry and the limits of capitalist production
Keywords: Educação; Semiformação; Trabalho e tempo livre; Crise do capitalismo; Education; Half formation; Work and free time; Crisis of capitalism; CIENCIAS HUMANAS::EDUCACAO